In search for Tiebout's mechanism "vote with their feet" in Bavaria - Angela Münch (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2011)
This paper analysis the possible demand for nature conservation within the Bavarian population. Drawing on the approach of revealed preferences and the mechanism of vote with their feet of Tiebout (1956) migration patterns in Bavarian counties are examined in more detail in order to assess the role of biodiversity for migration decision according to gender and age. The results show a clear pattern for the demand for natural amenities within the migration decision. However, other factors as e.g. employment option are not to neglect as they may even out-weight the demand for biodiversity.
Keywords: Q21; J61; 330; migration; biodiversity; Bavaria; Naturschutz; Biodiversität; Offenbarte Präferenzen; Binnenwanderung; Abwanderung und Widerspruch; Bayern